Pengaruh Suku Bunga, Loan to Deposit Ratio (LDR) dan Pertumbuhan Kredit terhadap Inflasi di Indonesia - Putri Yeni; Syamsul Amar; Alpon Satrianto (Universitas Negeri Padang, 2018)
This study aims to analyze the influence of interest rates, Loan to Deposit Ratio (LDR) and credit growth to inflation in Indonesia. This type of research is descriptive research and uses secondary data in the form of time-series from 2007 to 2016 using the method of multiple linear regression analysis. The results of this study indicate that interest rates have a significant and positive effect on inflation in Indonesia. The Loan to Deposit Ratio (LDR) has a significant and positive effect on inflation in Indonesia. Credit growth has a significant and positive effect on inflation in Indonesia. Based on the results of this study it can be concluded that there is a significant influence between interest rates, Loan to Deposit Ratio (LDR) and credit growth to inflation in Indonesia. Keyword: Inflation, Interest Rate, Loan to Deposit Ratio (LDR), Credit Growth